Equilibrium with Non-Convex Transactions Costs: Monetary and Non-Monetary Economies - Heller, Walter Perrin; Starr, Ross M. (Review of Economic Studies, 1976)
Journal Article Equilibrium with Non-convex Transactions Costs: Monetary and Non-monetary Economies Get access Walter Perrin Heller, Walter Perrin Heller University of California, San Diego Search for other works by this author on: Oxford Academic Google Scholar Ross M. Starr Ross M. Starr University of California, Davis Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 43, Issue 2, June 1976, Pages 195–215, https://doi.org/10.2307/2297318 Published: 01 June 1976